2016
DOI: 10.3892/or.2016.4710
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β2-adrenergic receptor reduces triple-negative breast cancer brain metastases: The potential benefit of perioperative β-blockade

Abstract: In response to recent studies, we investigated an association between perioperative β-blockade and breast cancer metastases. First, a retrospective study examining perioperative β-blocker use and cancer recurrence and metastases was conducted on 1,029 patients who underwent breast cancer surgery at the City of Hope Cancer Center between 2000 and 2010. We followed the clinical study and examined proliferation, migration, and invasion in vitro of primary and brain-metastatic breast cancer cells in response to β2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 32 publications
3
76
0
Order By: Relevance
“…No matter what the therapeutic intervention, however, HNSCC is still associated with a high rate of recurrence [113,114]. In addition, metastatic disease remains the principal cause of death in cancer [115,116]. Cell migration and invasion are fundamental steps of the metastatic phenomenon [117,118].…”
Section: Carbon Ion Irradiation Counteracts Cancer Stem Cells' Migratmentioning
confidence: 99%
“…No matter what the therapeutic intervention, however, HNSCC is still associated with a high rate of recurrence [113,114]. In addition, metastatic disease remains the principal cause of death in cancer [115,116]. Cell migration and invasion are fundamental steps of the metastatic phenomenon [117,118].…”
Section: Carbon Ion Irradiation Counteracts Cancer Stem Cells' Migratmentioning
confidence: 99%
“…Işeri et al (24) identified that propranolol and ICI 118,551 (selective β 2 -blockers) inhibited the invasion and migration of non-stimulated breast cancer cells (MCF-7) in vitro. In addition, Choy et al (25) demonstrated that propranolol treatment of triple-negative brain-metastatic cells (MDA-MB-231 Br) decreased the development of brain metastases in vivo. β-blockers have been identified to be beneficial to the survival of patients with TNBC; however, the antitumor mechanism involved remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic data compiled from breast cancer outcomes of patients on chronic b-blocker therapy had a 57% reduced risk of metastasis and 71% reduction in mortality after 10 years (Powe et al, 2010). A subsequent study discovered brain metastasis derived from breast cancer cells have increased b2-AR mRNA and protein expression levels, and exhibit enhanced cell proliferation and migration (Choy et al, 2016). Chronic b-AR activation induced by stress promotes colon cancer metastasis (Zhao et al, 2015), possibly through transactivation of the epidermal growth factor receptor-Akt/ extracellular signal-regulated kinase pathway (Chin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%